2011
DOI: 10.1128/jvi.02493-10
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Antigen Receptor-Derived Signals Support Sustained Surveillance of the Lungs by Pathogen-Specific Cytotoxic T Lymphocytes

Abstract: Viral infections often gain access to the body of their host by exploiting areas of natural vulnerability, such as the semipermeable surfaces of mucosal tissues which are adapted for adsorption of nutrients and other diffusible molecules. Once the microbes have crossed the epithelial barrier, they can disperse to other tissues where eradication may not be possible. The best opportunity for successful immune intervention is immediately after infection while the pathogen is confined to a localized area of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
232
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(249 citation statements)
references
References 49 publications
(77 reference statements)
16
232
1
Order By: Relevance
“…Interestingly, Ag recognition and exposure to type I IFN do not appear to be strictly required for CD69 induction in T cells, consistent with the observation that T RM cells can form in the absence of local Ag recognition or overt inflammation (3,(5)(6)(7). Nevertheless, given the strong induction of CD69 expression by Ag stimulation and exposure to inflammatory cytokines, it appears likely that such signals cooperate to support effector T cell retention and T RM cell generation (2,6,12,19). Overall, our results define the early induction of CD69 expression as an important checkpoint in peripheral effector T cell retention and the generation of long-lived immune memory at body surfaces.…”
Section: Cd69 Interference With S1p Receptor Function Regulates T Celsupporting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, Ag recognition and exposure to type I IFN do not appear to be strictly required for CD69 induction in T cells, consistent with the observation that T RM cells can form in the absence of local Ag recognition or overt inflammation (3,(5)(6)(7). Nevertheless, given the strong induction of CD69 expression by Ag stimulation and exposure to inflammatory cytokines, it appears likely that such signals cooperate to support effector T cell retention and T RM cell generation (2,6,12,19). Overall, our results define the early induction of CD69 expression as an important checkpoint in peripheral effector T cell retention and the generation of long-lived immune memory at body surfaces.…”
Section: Cd69 Interference With S1p Receptor Function Regulates T Celsupporting
confidence: 61%
“…As a consequence, CD69 induction can block S1P-mediated T cell egress from lymphoid tissues (17). Despite this, following virus infection, peak numbers of circulating Cd69 2/2 effector CD8 T cells appear normal (3,18,19). Although such results indicate that CD69-dependent regulation of S1P 1 -mediated egress from lymph nodes (LNs) may have surprisingly little impact on the expansion of virus-specific CD8 T cells, we showed recently that CD69 expression is required for optimal T RM cell formation in nonlymphoid tissues, such as skin and dorsal root ganglia, following infection with HSV (3).…”
mentioning
confidence: 99%
“…Thus, the ability to support efficient T RM lodgement by local inflammation and their long-term persistence in the absence of ongoing antigen-presentation expands the potential use of this population in infection control. It means that T RM cells can be used to protect the epithelial surfaces that form key pathogen entry points in the body without the use of vectors that drive ongoing presentation, as is otherwise necessary for effective peripheral immunity based on circulating memory T cells (9,34,42).…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanistic standpoint, others have shown that TGFβ production in certain tissues promotes CD103 expression, either soluble TGFβ or membrane‐bound TGFβ (Casey et al., 2012; Lee et al., 2011; Mackay et al., 2013; Yu et al., 2013). Our studies build on this foundation to demonstrate that signaling through TGFβ bound to the membrane of endometrial DCs was responsible for the induction of CD103 on naïve CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%